Bedtime Routines Intervention for Children (BRIC) using an automated text messaging system for behaviour change: study protocol for an early phase study - Kitsaras, George (Pilot Feasibility Stud, 2020)
BACKGROUND: This work concerns the activities in the last hour before bed for young children born to first-time parents, so called bedtime routines (BTR). These activities include amongst others tooth brushing, reading a book, having a bath and avoiding food and drinks before bed. Having a set bedtime at a suitable hour is also very important. Establishing good bedtime routines has been shown to be really important for a number of health, wellbeing, development and social outcomes. Currently, there is no evidence-based bedtime routine intervention for first-time parents using a novel design (i.e. text messages). Existing research has highlighted the importance of bedtime routines and the lack of appropriate mechanisms in place for parents who sought support. METHODS: The proposed study includes 2 work packages. Work package 1 focuses on the development of the intervention through a combination of qualitative work (1:1 interviews with parents on barriers and facilitators on bedtime routines using the Theoretical Domains Framework) and an expert group of key stakeholders. Work package 2 involves a small-scale (n = 50) feasibility and effectiveness study to examine proof of concept with first-time parents using text messages to communicate the intervention. Quantitative information relating to uptake, engagement, retention and effectiveness of the intervention as well as qualitative information (focus groups with parents who took part in the study) will be collected. Overall, the effectiveness of the intervention will be assessed through the APEASE criteria (acceptability, practicability, effectiveness, affordability, safety, equity). DISCUSSION: This study can provide initial yet important support for further exploration in the field of bedtime routines in more complicated family structures (parents with more than 1 child, separated families etc.). Also, the implementation of a novel study design (i.e. text messages) could lead to considerable cost savings while maintaining high retention, uptake and engagement from the participants. Should the intervention meet the APEASE criteria, a more comprehensive intervention on bedtime routines for first-time parents will be explored in a more robust (RCT and longitudinal) approach. TRIALS REGISTRATION: Due to the nature of the study, no trial registration is currently in place.